Dissecting the Causal Mechanism of X-Linked Dystonia-Parkinsonism by Integrating Genome and Transcriptome Assembly. - Aneichyk, Tatsiana; Hendriks, William T; Yadav, Rachita; Shin, David; Gao, Dadi; Vaine, Christine A; Collins, Ryan L; Domingo, Aloysius; Currall, Benjamin; Stortchevoi, Alexei; Multhaupt-Buell, Trisha; Penney, Ellen B; et al. (Cell, 2018)
X-linked Dystonia-Parkinsonism (XDP) is a Mendelian neurodegenerative disease that is endemic to the Philippines and is associated with a founder haplotype. We integrated multiple genome and transcriptome assembly technologies to narrow the causal mutation to the TAF1 locus, which included a SINE-VNTR-Alu (SVA) retrotransposition into intron 32 of the gene. Transcriptome analyses identified decreased expression of the canonical cTAF1 transcript among XDP probands, and de novo assembly across multiple pluripotent stem-cell-derived neuronal lineages discovered aberrant TAF1 transcription that involved alternative splicing and intron retention (IR) in proximity to the SVA that was anti-correlated with overall TAF1 expression. CRISPR/Cas9 excision of the SVA rescued this XDP-specific transcriptional signature and normalized TAF1 expression in probands. These data suggest an SVA-mediated aberrant transcriptional mechanism associated with XDP and may provide a roadmap for layered technologies and integrated assembly-based analyses for other unsolved Mendelian disorders.
Keywords: Alternative Splicing; Alu Elements; Base Sequence; Cohort Studies; CRISPR-Cas Systems; Dystonic Disorders; Family; Female; Genetic Diseases, X-Linked; Genetic Loci; Genome, Human; Haplotypes; High-Throughput Nucleotide Sequencing; Histone Acetyltransferases; Humans; Induced Pluripotent Stem Cells; Introns; Male; Minisatellite Repeats; Models, Genetic; Nerve Degeneration; Neural Stem Cells; Neurons; RNA, Messenger; Short Interspersed Nucleotide Elements; TATA-Binding Protein Associated Factors; Transcription Factor TFIID; Transcriptome

Recessive loss of function of the neuronal ubiquitin hydrolase UCHL1 leads to early-onset progressive neurodegeneration. - Bilguvar, Kaya; Tyagi, Navneet K; Ozkara, Cigdem; Tuysuz, Beyhan; Bakircioglu, Mehmet; Choi, Murim; Delil, Sakir; Çağlayan, Ahmet O; Baranoski, Jacob F; Erturk, Ozdem; Yalcinkaya, Cengiz; Karacorlu, Murat; et al. (Proc Natl Acad Sci U S A, 2013)
Ubiquitin C-terminal hydrolase-L1 (UCHL1), a neuron-specific de-ubiquitinating enzyme, is one of the most abundant proteins in the brain. We describe three siblings from a consanguineous union with a previously unreported early-onset progressive neurodegenerative syndrome featuring childhood onset blindness, cerebellar ataxia, nystagmus, dorsal column dysfuction, and spasticity with upper motor neuron dysfunction. Through homozygosity mapping of the affected individuals followed by whole-exome sequencing of the index case, we identified a previously undescribed homozygous missense mutation within the ubiquitin binding domain of UCHL1 (UCHL1(GLU7ALA)), shared by all affected subjects. As demonstrated by isothermal titration calorimetry, purified UCHL1(GLU7ALA), compared with WT, exhibited at least sevenfold reduced affinity for ubiquitin. In vitro, the mutation led to a near complete loss of UCHL1 hydrolase activity. The GLU7ALA variant is predicted to interfere with the substrate binding by restricting the proper positioning of the substrate for tunneling underneath the cross-over loop spanning the catalytic cleft of UCHL1. This interference with substrate binding, combined with near complete loss of hydrolase activity, resulted in a >100-fold reduction in the efficiency of UCHL1(GLU7ALA) relative to WT. These findings demonstrate a broad requirement of UCHL1 in the maintenance of the nervous system.
Keywords: Adult; Age of Onset; Amino Acid Sequence; Base Sequence; Child, Preschool; Exome; Female; Genes, Recessive; Homozygote; Humans; Hydrolysis; Male; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Nerve Degeneration; Neurons; Pedigree; Protein Binding; Sequence Analysis, DNA; Substrate Specificity; Syndrome; Thermodynamics; Ubiquitin; Ubiquitin Thiolesterase